The Liveworksheet-Based E-LKPD Feasibility Test to Improve Critical Thinking Skills of Class V Students on Ecosystem Materials - Nur ‘Aini Alfi Ulyatin; Ali Formen; Agung Tri Prasetya; Putut Parwoto (Postgraduate, University of Mataram, 2023)
This research aims to create an E-LKPD supported by live worksheets to improve students' thinking skills regarding ecosystem material suitable for improving Natural Sciences (IPA) learning. The E-LKPD development method uses ADDIE which consists of 5 stages: (1) Analysis, (2) Design, (3) Development, (4) Evaluation. However, this research is only limited to development. The e-LKDP acceptance criteria are based on the assessment of 5 fifth-grade elementary school teachers. Data analysis uses quantitative descriptive methods. Validity criteria are determined from the validation results of Class V teachers who obtained the average percentage. The results of research data analysis show that e-LKPD developed using live LKS has an average score of 78.46%, which shows that it is suitable to be used as effective learning teaching material to improve students' thinking abilities.